Precision diagnostics of pulsation and evolution in helium-rich low-mass stars - MARTIN, PAMELA (Trinity College Dublin. School of Physics. Discipline of Physics, 2019)
In this thesis we discuss many types of low mass stars linked by their unusually low hydrogen atmospheric abundance, usually completely replaced with helium. We begin with the hot subdwarfs; subdwarf O and B (sdB, sdO) stars are low-mass core helium burning stars with extremely low-mass hydrogen envelopes. Their atmospheres are generally helium deficient; how- ever a minority have extremely helium-rich surfaces. An additional fraction have an intermediate surface-helium abundance, occasionally accompanied by peculiar abundances of other elements. LSIV−14◦116 is a non-radially pulsating slowly-rotating chemically-peculiar helium-rich sdB with a 4 dex surface excess of zirconium, yttrium, and strontium. The pulsations are un- expected and unexplained, as the star is 6 000K hotter than the blue edge of the hot subdwarf g-mode instability strip. The presence of pulsations offers a rare opportunity to study the structure of the photosphere. Using a time series of ultraviolet and visual spectra from the Very Large Telescope (VLT) we have measured high precision radial velocities in individual spectral lines throughout the entire spectrum. We confirm that the presence of the photometric variability results in the physical motion of the photo- sphere, resolving the different layers proves difficult due to the horizontal nature of the propagation of a gravity wave. In the case of BX Cir, a short-period pulsating extreme helium supergiant, the absence of hydrogen opacity allows us to see deeper into the atmosphere than in any other star. High resolution spectra from the Southern African Large Telescope (SALT) has allowed us to apply the methodology developed for LSIV−14◦116 to resolve the motion in the atmosphere of BX Cir. Our aim was to resolve the motion of different layers within the photosphere, and the passage of the outward travelling waves. We have investigated the kinematics of three groups of hot subdwarf stars to determine whether they belong to similar or different Galactic populations. We confirm that the majority of helium-deficient subdwarfs show a kinematic distribution similar to that of thick disk stars. Helium-rich sdBs show a more diverse kinematic distribution. Although the majority are probably disk stars, a minority show a much higher velocity dispersion consistent with membership of a Galactic halo population. Since the discovery of R Coronae Borealis in 1795, several classes of hydrogen-deficient stars have been identified (Jeffery, 2008) but, despite their great intrinsic brightness, their members are so rare that virtually all lie at distances too great to measure directly from the ground. Reliable measurements have only become possible for a significant number following the second release of data from the astrometric space mission Gaia. Following this data release the new parallax measurements and more precise proper motions have allowed us to calculate the Galactic space velocities and orbits for over 200 hydrogen-deficient low-mass stars. Distances, and hence luminosities, are critical for explaining the origin and life histories of stars which possess so little surface hydrogen that, in several cases, its abundance cannot be measured. We discuss the formation and evolution of some of the rarest stars in the Galaxy.
APPROVED
Keywords: stars: chemically peculiar; stars: hot subdwarf; stars: kinematics and dynamics; stars: pulsation